Bicol College Ed. D. and Ph. D. Graduates from 2012-2021: A Tracer Study - Esparrago, Milagros (JPAIR Institutional Research, 2022)
A school tracer study is a research method used to track the progress and outcomes of a school’s graduates over time. In addition, school tracer studies can help to identify trends and patterns in education and employment outcomes across different countries and regions, allowing for cross-country comparisons and the identification of best practices. A tracer study on the Master of Science Graduates in Disaster Risk Management of the Central Bicol State University of Agriculture determined the employability of the Master of Science in Disaster Risk Management (MSDRM) graduates to provide input to curriculum innovation. The majority of the tracer studies reviewed were from the undergraduate and master’s levels. This tracer study on graduates of the doctoral programs, EdD and PhD of Bicol College Inc. is a novel undertaking. The descriptive–quantitative research design was used employing the saturated sampling technique. A database of these graduates was established, and it was found that lifelong learning and service to the community are very relevant among doctoral degree graduates. Open career for postdoctoral studies is a challenge to them. Results showed that the majority of the respondents are females, with ages ranging from 40-60 years old. It took them 3-5 years to complete the degree, enroll in the degree program for professional growth and mostly be promoted after completion. Ten respondents obtained recognition and awards at the local, regional, national, and international level. One graduate even passed the Career Executive Service Written Examination, a qualification for directorship.